Approximated unimodal region elimination-based global optimisation method for engineering design. (28th May 2009) - Younis, Adel; Xu, Ruoning; Dong, Zuomin
Computer analysis and simulation-based design optimisation requires more computationally efficient global optimisation tools. In this work, a new global optimisation algorithm based on design experiments, region elimination and response surface modelling, namely, the Approximated Unimodal Region Elimination (AUMRE) method, is introduced. The approach divides the field of interest into several unimodal regions using design experiment data, identifies and ranks the regions that most likely contain the global minimum, forms a response surface model using additional design experiment data over the most promising region, identifies its minimum, removes this processed region and moves to the next most promising region. By avoiding redundant searches, the approach identifies the global optimum with a reduced number of objective function evaluations and computation effort. The new algorithm was tested using a variety of benchmark global optimisation problems and compared with several widely used global optimisation algorithms. The results present a comparable search accuracy and superior computation efficiency, making the new algorithm an ideal tool for computer analysis and simulation-based global design optimisation.